Predictive hyperglycemia and hypoglycemia minimization: In‐home double‐blind randomized controlled evaluation in children and young adolescents. Issue 3 (20th November 2017) - Forlenza, Gregory P; Raghinaru, Dan; Cameron, Faye; Wayne Bequette, B; Peter Chase, H; Paul Wadwa, R; Maahs, David M; Jost, Emily; Ly, Trang T; Wilson, Darrell M; Norlander, Lisa; Ekhlaspour, Laya; et al.
Abstract : Objective: The primary objective of this trial was to evaluate the feasibility, safety, and efficacy of a predictive hyperglycemia and hypoglycemia minimization (PHHM) system vs predictive low glucose suspension (PLGS) alone in optimizing overnight glucose control in children 6 to 14 years old. Research Design and Methods: Twenty‐eight participants 6 to 14 years old with T1D duration ≥1 year with daily insulin therapy ≥12 months and on insulin pump therapy for ≥6 months were randomized per night into PHHM mode or PLGS‐only mode for 42 nights. The primary outcome was percentage of time in sensor‐measured range 70 to 180 mg/dL in the overnight period. Results: The addition of automated insulin delivery with PHHM increased time in target range (70‐180 mg/dL) from 66 ± 11% during PLGS nights to 76 ± 9% during PHHM nights ( P <.001), without increasing hypoglycemia as measured by time below various thresholds. Average morning blood glucose improved from 176 ± 28 mg/dL following PLGS nights to 154 ± 19 mg/dL following PHHM nights ( P <.001). Conclusions: The PHHM system was effective in optimizing overnight glycemic control, significantly increasing time in range, lowering mean glucose, and decreasing glycemic variability compared to PLGS alone in children 6 to 14 years old.